Intestinal microbiota and Anorexia Nervosa - Borenski, Grzegorz; Wojcik, Magdalena; Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Eating disorders are severe psychiatric disorders. Anorexia nervosa (AN) has a mortality rate among the highest of any psychiatric illnesses. Anorexia nervosa is characterised by extreme weight loss and fear of gaining weight. Lifestyle and diet have a major influence on gut microbiota composition. Thus, studies of this subject may have potential in better understanding pathophysiology of AN. The aim of the study: The purpose of this systemic review was to collect and analyse available data about correlations between anorexia nervosa and gut microbiota. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: anorexia nervosa, gut microbiota, diet. Description of the state of knowledge: Intestinal microbiota plays an important role in weight regulation. Alterations in bidirectional brain-gut microbiota interactions can be responsible for a number of diseases including irritable bowel syndrome or functional gastrointestinal disorders. Studies show differences of gut microbiota composition between AN patients and normal-weight control groups. Composition of intestinal microbiota changes during nutritional rehabilitation. However, the differences between AN and control groups are still present even after substantial weight gain. Moreover, some correlations according to BMI are observed. Also there might be a correlation between increased intestinal permeability and gastrointestinal complaints common in AN. Summary: Studies showed alterations in intestinal microbiota composition in anorexia nervosa patients comparing to normal-weight individuals. However, more studies of this subject are needed. Knowing more correlations between gut microbiota, diet and weight may be helpful in understanding anorexia nervosa and improving its treatment.